Translation and validation of the Malay version of the cognitive emotion regulation questionnaire (CERQ-M) in Malaysian adults - Azahar, Nur Hani Liyana Kamarul (2021)
Introduction: Coping strategies are important for any individual to manage stressful and negative experiences, and Cognitive coping strategies have been suggested to be the one of the most effective coping strategies. However, objective measurement for cognitive coping is unavailable in Bahasa Malaysia for the Malaysian adult population. This study aims to translate the CERQ, a measure of cognitive coping strategies into Bahasa Malaysia, and investigate the validity of the CERQ model to apply to the Malaysian population. Validation of the CERQ-M is anticipated to facilitate practitioners in identifying the cognitive coping strategies among Malaysian adults. Methodology: In Phase 1, the CERQ-M was translated into Malay and reviewed by three expert panels. Pre-testing of the questionnaire was conducted on 10 participants to evaluate its content validity. The translated CERQ-M was distributed through an online questionnaire platform to 260 participants throughout Malaysia in Phase 2. Results: The translation of CERQ into Bahasa Malaysia was achieved. Face validity and Content validity was determined. Overall, the reported frequently used cognitive coping by rank is Positive Reappraisal and Refocus on Planning. CERQ-M reported high internal consistency (α =.891) and no extreme outliers were detected. However, Confirmatory Factor Analysis on the model discovered the original CERQ Nine-Factor model was below acceptable fit. A more fitting fit was revealed when Item 20 was modified to be under Rumination rather than under the original Acceptance cognitive strategy. The modified Nine-Factor model indices criterion value was satisfactory (RMSEA ≤ 0.08, (SRMR) <0.10, (CFI) >0.80). Conclusion: The CERQ-M is a valid and acceptable objective measure of cognitive coping strategies in the Malaysian adult population. However, findings suggest for further research to explore the factors in the CERQ-M to develop a better CERQ-M model fit for the local population.